(untitled) (Phenomenology, Humanities and Sciences, 2023)
This theoretical essay aims to consider reading possibilities from the strategy of deconstruction inspired by Jacques Derrida’s thinking, constructing itself as a methodological foray and as intended to contribute to epistemological discussion about research on the phenomenon (or the Discourse) in Humanities. At first, clues are proposed for a Derridean reading of the phenomenon that, as such, demonstrates a textual structure. To this end, the essay starts from the centrality of the concept of Différance and how it circumscribes the possibility of an object for deconstructionist strategy analysis – i.e., the errancy of meaning, which simultaneously considers its dynamic and structure. In the following, this perspective of reading is defined as a strategy of analysis/reading of the lifeworld, showing how can contribute the concept of reality as a text to such discussion. Finally, a synthesis of the fundamental elements of this strategy is outlined. This essay concludes with the suggestion that the everyday lieworld is made up of a history of contingencies and crossings and of a verticality that, without committing to the idea of a last Arché, has a center that, however, is not identical to subjectivity, but is its producer – the very structure and dynamics of the Différance.